2022
DOI: 10.1021/acschemneuro.2c00325
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis and Development of Notum Fragment Screening Hits

Abstract: The Wnt signaling suppressor Notum is a promising target for osteoporosis, Alzheimer's disease, and colorectal cancers. To develop novel Notum inhibitors, we used an X-ray crystallographic fragment screen with the Diamond-SGC Poised Library (DSPL) and identified 59 fragment hits from the analysis of 768 data sets. Fifty-eight of the hits were found bound at the enzyme catalytic pocket with potencies ranging from 0.5 to >1000 μM. Analysis of the fragments' diverse binding modes, enzymatic inhibitory activities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Compounds were individually soaked into crystals of Notum and high-resolution structures were determined for each of these putative Notum–fragment complexes. The electron density maps provided evidence of compound binding associated with the active site of Notum for 59 of the crystal structures (hit rate: 7.7%). ,, The complete output of the hits from this crystallographic screen with the DPSL will be published separately. , Hit validation was then performed by demonstration that these binders were able to inhibit Notum carboxylesterase activity in a biochemical assay (up to 1 mM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds were individually soaked into crystals of Notum and high-resolution structures were determined for each of these putative Notum–fragment complexes. The electron density maps provided evidence of compound binding associated with the active site of Notum for 59 of the crystal structures (hit rate: 7.7%). ,, The complete output of the hits from this crystallographic screen with the DPSL will be published separately. , Hit validation was then performed by demonstration that these binders were able to inhibit Notum carboxylesterase activity in a biochemical assay (up to 1 mM).…”
Section: Resultsmentioning
confidence: 99%
“…23,26,41 The complete output of the hits from this crystallographic screen with the DPSL will be published separately. 42,43 Hit validation was then performed by demonstration that these binders were able to inhibit Notum carboxylesterase activity in a biochemical assay (up to 1 mM).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notum (Wingful), a palmitoleoyl-protein carboxylesterase, is a secreted antagonist of Wingless (Wg, Drosophila Wnt1), encoding an α/β-hydrolase enzyme with similarity to pectin acetylesterases from plants [ 6 8 ]. It is reported that Notum influences Wingless protein distribution by modifying cell surface proteoglycans and is induced by high levels of Wingless signaling at the same time [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The heterocyclic compounds, characterized by five or sixmembered rings containing at least one, but not limited to, an atom of nitrogen, oxygen, and sulfur, generally display bioactivity as medicine and pesticides. The heterocycle moieties were demonstrated for interaction with the target site in medicinal chemistry and biochemistry [1][2][3]. Chemical active ingredients usually give excellent antibacterial, anti-inflammatory, and anti-tumor activities if structurally introduced or replaced by heterocyclic fragments [4][5][6].…”
Section: Introductionmentioning
confidence: 99%